The Effectiveness of Prone and Supine Nesting Positions on Changes of Oxygen Saturation and Weight in Premature Babies - Ayu Prawesti; Etika Emaliyawati; Ristina Mirwanti; Aan Nuraeni (Universitas Airlangga, 2019)
Introduction: Stress experienced by the baby will affect the body’s function by increasing the body’s metabolism. Nesting is used to reduce stress in premature babies. Nesting can be done in a supine or prone position. Few studies have examined the effects of body position on body weight and oxygen saturation. The objective of the study was to determine the difference in oxygen saturation and weight change on the use of nesting in the prone and supine positions in premature babies.Methods: The research used a quasi-experimental design. The sample consisted of 30 premature babies, which was obtained using a consecutive sample technique. The independent variables were nesting positioning (supine and prone), and the dependent variables were oxygen saturation and body weight. The data of oxygen saturation and the baby’s weight were collected using pulse oximetry; the baby’s weight scale used observation sheets. The data was analysed using the t-test, Wilcoxon Sign Ranks Test, and Mann Whitney U Test.Results: The results showed that there was a difference in oxygen saturation before and after the use of nesting in the supine (p=0.001) and prone position (p=0.000). There was a weight difference before and after the use of nesting in both supine (p=0.000) and prone position (p=0.000). There was no difference in oxygen saturation value and infant weight, before or after, between the supine position and the prone position (p=0.18; p=0.9).Conclusion: The use of nesting in both positions (supine or prone) can increase oxygen saturation and infant weight. Researchers recommend the use of nesting with supine or prone positions routinely in premature babies.